The Role of Microglia and Astrocytes in the Neuroinflammation Process in Acute Ischaemic Stroke - Dianing Aluh Qomala; I Ketut Wisnuaji Jayawardhana; Lalu Hizrian Abtartu; Rabsanjani Rabsanjani; Ilsa Hunaifi (Research of Service Administration Health and Sains Healthys, 2025)
Acute ischemic stroke triggers a complex neuroinflammatory response involving resident glial cells, particularly microglia and astrocytes. Microglia rapidly activate following ischemia and polarize into two main phenotypes: the pro-inflammatory M1 phenotype, which exacerbates neuronal damage through the release of cytokines like TNF-α, IL-1β, and reactive oxygen species (ROS), and the anti-inflammatory M2 phenotype, which promotes tissue repair via IL-10 and IL-4 secretion. Astrocytes also play a dual role: in the acute phase, they exert neuroprotective effects by regulating glutamate homeostasis, producing antioxidants (e.g., glutathione and superoxide dismutase), and supporting neurogenesis and angiogenesis; however, in the chronic phase, reactive astrocytes contribute to glial scar formation, which inhibits axonal regeneration. The dynamic interplay between microglia and astrocytes critically shapes the neuroinflammatory milieu—determining whether the response is protective or detrimental. Understanding these dual roles offers promising avenues for developing neuroprotective therapies targeting neuroinflammation after acute ischemic stroke.